Direct coupling of oligomerization and oligomerization-driven endocytosis of the dopamine transporter to its conformational mechanics and activity - Sorkina, Tatiana (J Biol Chem, 2021)
Dopamine transporter (DAT) mediates the reuptake of synaptically released dopamine, and thus controls the duration and intensity of dopamine neurotransmission. Mammalian DAT has been observed to form oligomers, although the mechanisms of oligomerization and its role in DAT activity and trafficking remain largely unknown. We discovered a series of small molecule compounds that stabilize trimers and induce high-order oligomers of DAT and concomitantly promote its clathrin-independent endocytosis. Using a combination of chemical cross-linking, fluorescence resonance energy transfer microscopy, antibody-uptake endocytosis assay, live-cell lattice light sheet microscopy, ligand binding and substrate transport kinetics analyses, and molecular modeling and simulations, we investigated molecular basis of DAT oligomerization and endocytosis induced by these compounds. Our study showed that small molecule–induced DAT oligomerization and endocytosis are favored by the inward-facing DAT conformation and involve interactions of four hydrophobic residues at the interface between transmembrane (TM) helices TM4 and TM9. Surprisingly, a corresponding quadruple DAT mutant displays altered dopamine transport kinetics and increased cocaine-analog binding. The latter is shown to originate from an increased preference for outward-facing conformation and inward-to-outward transition. Taken together, our results demonstrate a direct coupling between conformational dynamics of DAT, functional activity of the transporter, and its oligomerization leading to endocytosis. The high specificity of such coupling for DAT makes the TM4-9 hub a new target for pharmacological modulation of DAT activity and subcellular localization.